2002
DOI: 10.1111/1467-8608.00254
|View full text |Cite
|
Sign up to set email alerts
|

The ethical benefits of trust‐based partnering: the example of the construction industry

Abstract: As inter‐organisational relations represent an increasingly important element in business the ability to build sustainable relationships becomes a key skill. To achieve sustainable relationships parties need to move from a low trust/low ethics base to a high trust/high ethics base in their relating. This paper uses data from a study into trust‐based partnering in the construction industry to demonstrate that ethics is integral to trust building. The data supports the proposition that ethical partnering, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 23 publications
0
36
1
1
Order By: Relevance
“…The need to build trust and ethics together has been remarked upon by Wood et al (2002). Trust demands high ethical standards; trust is an ethical construct.…”
Section: Theories On Trustmentioning
confidence: 99%
“…The need to build trust and ethics together has been remarked upon by Wood et al (2002). Trust demands high ethical standards; trust is an ethical construct.…”
Section: Theories On Trustmentioning
confidence: 99%
“…Svensson et al (2009) advise that both suppliers and customers be informed of the existence and functions of codes of ethics. Wood et al (2002) found that CoEs are usually communicated to these two groups, whether formally or informally, to some extent. However, the extent to which the standards of these codes are met across the supply chain remains an unanswered question.…”
Section: Relating Coes To Suppliers and Subcontractorsmentioning
confidence: 99%
“…Emphasis in these discussions should be placed in organisational values and value expectations, thus helping employees to make decisions in accordance with those values should ethical dilemmas arise. According to Svensson et al (2009), ethical dilemmas arising in the marketplace can also be resolved by CoEs, and Wood et al (2002) reported that approximately 50 % of the organisations they surveyed claimed to use their CoEs for just that purpose.…”
Section: Creating Forums To Discuss Ethical Dilemmasmentioning
confidence: 99%
“…Love et al, 2004) and trust and partnering (e.g. Wood et al, 2002;Khalfan et al, 2007). Finally, somewhere between radical change and fluent adoption, new theories, concepts and notions can confront CM's domain boundaries and initiate debates as to whether a new perspective can be allowed to be incorporated legitimately into the existing domain.…”
Section: Outline Of This Thesismentioning
confidence: 99%
“…Examples of this include: the use of transaction costs (Winch 1989); supply chain , Love, Irani et al 2004; and, trust and partnering (Wood, McDermott et al 2002, Khalfan, McDermott et al 2007). On the other hand, theories and notions can stall at the boundary of the construction management domain, as happened with my HRO phenomenon.…”
Section: Concepts To Guide Evaluation Of Vdc Solutions: the Hro Lensmentioning
confidence: 99%